2016
DOI: 10.1111/ger.12222
|View full text |Cite
|
Sign up to set email alerts
|

Glass–ceramics bonding in geriatric patients: comparison with young teeth

Abstract: In geriatric patients, the shear bond strength of glass-ceramics did not differ when compared to that of young controls. On the dentin surface, etch-rinse resin cements appear to be more appropriate for glass-ceramics bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Often ceramic veneers and full ceramic crowns must be fabricated to fulfil the aesthetic demands of patients with deteriorated anterior dentitions. A study by Turk et al revealed no significant differences in the shear bond strength values when glass ceramics were adhesively luted to teeth of older adults as compared to the younger population [19].…”
Section: Periodontal Therapy and Fixed Prosthodonticsmentioning
confidence: 96%
“…Often ceramic veneers and full ceramic crowns must be fabricated to fulfil the aesthetic demands of patients with deteriorated anterior dentitions. A study by Turk et al revealed no significant differences in the shear bond strength values when glass ceramics were adhesively luted to teeth of older adults as compared to the younger population [19].…”
Section: Periodontal Therapy and Fixed Prosthodonticsmentioning
confidence: 96%
“…[ 4 , 5 ] As one of the most important factors affecting debonding, the depths of preparation influence the percentage of enamel surface on the adhesive surfaces, which is crucial for maintaining enough bonding strength of laminate veneers. Previous in vitro studies have confirmed that the shear bond strength (SBS) of ceramic to enamel was higher than to dentin [ 6 , 7 ], and longitudinal studies have shown that the survival rate of laminate veneers after 10 years is more than 90% if the enamel bonding surface is sufficient [ 8 , 9 ]. However, the effects of enamel preservation on the shear bond strength (SBS) of laminate veneers have not been clearly quantified.…”
Section: Introductionmentioning
confidence: 99%